The Evaluation of Online Learning Modules to Increase the Capacity of Nurses and Midwives in Promoting Preconception Health in Primary Health Care Services at Tiara Kasih Sejati Hospital Pematangsiantar - Agnes Rya Sianturi; Chrismis Novalinda Ginting; Yolanda Eliza Putri Lubis (CV. Inara, 2022)
This study aims to find out how to develop an online learning module to increase the capacity of nurses and midwives in promoting preconception health in primary health care services at Tiara Kasih Sejati Hospital Pematangsiantar. This type of research is classified into descriptive research with a quantitative approach. The sample of this study amounted to 93 samples consisting of midwives and nurses. Data was collected by using counseling methods and giving questionnaires. Data analysis using univariate. The results showed the difference in the increase in respondents' knowledge of 4.34 so that the average score of respondents' knowledge before and before being given the online learning module increased from 9.52 to 13.86. The benefit of the module is to increase the perception of midwives and nurses in improving health preconceptions in primary health care settings by 75.3% of midwives and pediatric nurses increasing the promotion of health preconceptions in primary health care settings. The ability level of midwives and nurses in accessing online learning modules regarding preconception is 55.9% the best and 44.1% not good. The assessment of the quality of the online learning module given to midwives and nurses, midwives and nurses who rated it good was 77.4% and those who rated it bad were 22.6%. The nutritional needs needed during the preconception period are macronutrients and micronutrients.